2022
DOI: 10.3389/fendo.2022.896558
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Improves Human Sperm Motility by Enhancing Glycolysis and Activating L-Type Calcium Channels

Abstract: Until now, the molecular mechanisms underlining sperm motility defect causing male infertility are still poorly understood. Safe and effective compounds or drugs that can improve sperm motility are also very limited. Lysophosphatidic acid (LPA) is a naturally occurring phospholipid and a bioactive intermediate with multiple biological activities. It has been detected in various body fluids such as serum, plasma, saliva, tears, blister fluids, hen egg white, and ascites from patients with ovarian cancer. LPA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Further, there exists no significant relationship between human sperm motility and tyrosine phosphorylation 59 . Previous studies have reported that tyrosine phosphorylation shows a slow and gradual time-dependent increase during sperm capacitation 60 62 . In this study, Bay117082 induced an obvious increase in protein tyrosine phosphorylation at 60 min (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Further, there exists no significant relationship between human sperm motility and tyrosine phosphorylation 59 . Previous studies have reported that tyrosine phosphorylation shows a slow and gradual time-dependent increase during sperm capacitation 60 62 . In this study, Bay117082 induced an obvious increase in protein tyrosine phosphorylation at 60 min (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Thick arrows (up or down) indicate the alteration of substance after treatment with Bay117082 (yellow), LPS (blue), and etomoxir (purple); solid lines represent verified trends and dashed lines represent conjectural trends. The elements “sperm” and “mitochondria” were modified from our previous article 62 . …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…on the sperm membrane surface [ 12 , 29 ] and the phosphorylation level of the VSP protein in the sperm tail can differ widely [ 30 , 31 ]. Intracellular alkalinization is critical not only for sperm hyperactivation and acrosome reactions but also for basal sperm motility, as the ability of dynein to hydrolyze ATP and provide axial filament bending increases significantly with increasing pHi [ 32 , 33 ]. These pH-regulating proteins can be classified into two categories: (1) Membrane proteins that mediate H + transmembrane transport, including proton channels (Hv1), proton pumps, and Na + /H + exchangers (NHE); (2) Membrane proteins that mediate HCO 3 − ion transmembrane transport, including SLC4 family proteins, SLC26 family proteins, and cystic fibrosis transmembrane transduction regulators (CFTR) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ionic requirements and signaling pathways of mammalian sperm motility have been widely studied, but they are still not completely understood [ 56 , 57 ]. At the molecular level, sperm motility enhancement requires the activation of several signaling pathways, including but not limited to cAMP-dependent pathways, an increase in pHi, changes in [Ca 2+ ]i concentration, and hyperpolarization of the sperm plasma membrane potential [ 33 , 58 ].…”
Section: Discussionmentioning
confidence: 99%